The features of pathogenetically directed therapy for chronic pelvic pain syndrome in experimental condition - Rudenko, A. V.; Kostyev, F. I. (Journal of Education, Health and Sport, 2015)
Rudenko A. V., Kostyev F. I. The features of pathogenetically directed therapy for chronic pelvic pain syndrome in experimental condition. Journal of Education, Health and Sport. 2015;5(8):55-63. ISSN 2391-8306. DOI 10.5281/zenodo.22824 http://dx.doi.org/10.5281/zenodo.22824 https://pbn.nauka.gov.pl/works/601988 POL-index https://pbn.nauka.gov.pl/polindex/browse/article/article-1b41c63c-c463-4013-bd18-684b35de96a0 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A55-63 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.06.2015. Revised 15.07.2015. Accepted: 25.07.2015. UDC: 617.581-009.7-092.9-0.85+618.13-009.7-0.92.9-0.85 The features of pathogenetically directed therapy for chronic pelvic pain syndrome in experimental condition A. V. Rudenko, F. I. Kostyev Odessa National Medical University, Odessa Keywords: pudendopathy, experiment, model, pathogenesis, muscle relaxants, adrenergic agonists, neurotrophic drugs. Abstract Experimental methods for investigation were performed on 120 four-month age white mongrel male rats, by the sacral plexus damage in animals through the ligating the largest nerve of the plexus - sciatic nerve, which can be considered as a predictor of pudendopathy and adequate clinical experimental modeling of the prototype method. The experimental animals after 1 month. of modeling were taken medications with muscle relaxant action of the central and peripheral activity and also neurotrophic effect. Comparative assessment of medicines was performed after 2.5 months. by morphological investigation of the pelvic floor and bladder, as well as biochemical analysis of blood, homogenates of the pelvic floor muscles and bladder, with assessment of the α2-macroglobulin, creatine kinase and lactate activity. The results showed that the pudendal nerve neuropathy in the experiment is accompanied by severe changes in the structure of the tissue of the bladder, pelvic floor muscles, nerve structures of the pelvis, as well as hypoxia, proteolysis and tissue destruction. The injection of drugs to experimental animals with reproduced pudendopathy revealed the different efficacy in restoring the structure of the detrusor muscle and the pelvic floor depending on effect of the drug.